EFFECT OF ATTENTION PARENTS, EMOTIONAL INTELLIGENCE, AND STUDENT ACHIEVEMENT MOTIVATION OF STUDENT LEARNING OUTCOMES IN ACCOUNTING SKILLS SMK PADANG OF WEST SUMATRA - Elen Lukmaneria; Yasri Yasri (Jurnal Kajian Pendidikan Ekonomi, 2015)
The problem in this research is : 1) how much influence parents' attention to the skills of emotional intelligence on Accounting Students , 2) How much parental influence on achievement motivation in Accounting Expertise Students , 3) how big is the influence of emotional intelligence on achievement motivation in Accounting Expertise Students, 4) how much influence parents' attention on learning outcomes in the Student Accounting Expertise, 5) how large the influence of emotional intelligence on learning outcomes on student Expertise accounting, 6) how much influence achievement motivation on learning outcomes in the Student accounting Expertise SMK Padang. This research is descriptive associative. The population were students in Accounting Skills Competency in SMK Negeri 2, 3, and 4 Padang totaling 809 people. Proportional sampling technique was purposive sampling insidential, with a sample of 268 students. Data analysis techniques are SEM analysis. The results showed that: 1) the attention of parents significantly influence emotional intelligence skills Accounting Students of SMK Negeri Padang, 2) a concern of parents tsiswa significant effect on achievement motivation in Accounting Expertise Students of SMK Negeri Padang, 3) a significant effect of emotional intelligence the achievement motivation in Accounting Expertise Students of SMK Negeri Padang, 4) parental significant effect on student learning outcomes in Accounting Expertise SMK Padang, 5) emotional intelligence no significant effect on student learning outcomes in Accounting Expertise SMK Padang, 6) achievement motivation has no significant effect on student learning outcomes in Accounting Expertise SMK Padang. Based on the above results, it can be concluded that to improve student learning outcomes in Accounting Expertise SMK Padang expected student learning environment, especially the family environment that is attention to more parents by providing supervision .Keywords : Attention Parents, Emotional Intelligence, And Student Achievement Motivation Of Student Learning Outcomes